Perancangan Sistem Informasi Buku Tamu Berbasis Web Pada Kantor Kementerian Hukum dan Hak Asasi Manusia Banda Aceh - Icha Widya Pratiwi; Nazaruddin Ahmad; Arifiyanto Hadinegoro; Saifan Hafizh; Rana Sulthanah (J-INTECH ( Journal of Information and Technology), 2024)
In an agency, visits from other institutions and the general public frequently occur. To record these visits, an officer manages a guest book where visitors log their presence and state their purpose. However, the conventional method of using a guest book is susceptible to damage and leads to the accumulation of physical books. Additionally, summarizing visit data daily, weekly, monthly, or annually becomes challenging. Therefore, there is a need for digital modernization of visitor recording to align with the smart government concept implemented in government agencies. The proposed solution is to design a web-based guest book information system that will facilitate visitor data recording, visit monitoring, and visit summarization according to the needs of the leadership at the Regional Office of Law and Human Rights in Banda Aceh. To achieve optimal results, this study employs the Research and Development (R&D) method combined with the waterfall software development approach. The design process includes creating use case diagrams, conceptualizing database table relations, and utilizing the PHP programming language with the Bootstrap framework to ensure an easy-to-use interface. With this guest book information system, visitors will no longer need to fill out conventional guest books, and the Regional Office of Law and Human Rights in Banda Aceh will not require traditional guest book archiving. All visitor data, visit logs, and visit summaries will be stored in a system accessible to relevant parties as needed.